Information application for data medical monitoring - Shevtsova, O.; Kasyanenko, W. (My University, 2018)
Analysis of the areas of application of data processing systems, in which splines playback algorithms are implemented, allows one to distinguish the following areas: – medical monitoring; – economic monitoring; – technical monitoring; – geophysical monitoring.
Keywords: вычислительная схема; обчислювальна схема; медичний контроль; медицинский контроль; медичний нагляд